Yigael Yadin on "Hazor, the Head of All Those Kingdoms" - Yadin, Yigaʾel 1917-1984 (1975)
The site of Hazor, located in upper Galilee, consists of a 30-acre upper tell, plus an adjacent plateau at a lower level of over 175 acres. The tell, unlike the plateau, was occupied almost continuously from the 27th century B.C. to the 2nd century B.C. By contrast, the plateau, or lower city, was a […]